Hammock effect and complete cusp prolapse: Rare mechanisms of Melody valve failure demonstrated by intracardiac echocardiography - Simone Jhaveri; Lourdes Prieto; Patcharapong Suntharos (Wolters Kluwer Medknow Publications, 2019)
Transcatheter pulmonary valve replacement using Melody valve (Medtronic, Minneapolis MN) has significantly increased in the recent decades. Melody valve failures, although rare, can be problematic and require re-intervention. Through intracardiac echocardiography, we present two patients who each had a rare etiology for dysfunction of their Melody valve. Hammock effect, wherein the valve does not oppose the stent and complete cusp failure causing severe regurgitation have not been previously described as causes of Melody valve failure in the absence of endocarditis. Awareness and knowledge of these mechanisms is pivotal in the management of this patient population.